Hak Kewarganegaraan dalam Perspektif Konstitusi Indonesia : Analisis Pasal 26 UUD 1945 yang Mengatur tentang Kewarganegaraan - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Athal Izdihar Parkash; Aisha Inda Nursifa; Devi Zahrotul Ulya (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This study explores the regulation of citizenship under Article 26 of the 1945 Constitution of Indonesia and its implications in the context of globalization. Article 26 defines who qualifies as an Indonesian citizen and provides a legal basis for more detailed citizenship regulations. In light of increased global mobility and complex international relations, new challenges have emerged that necessitate a reassessment of citizenship policies, particularly regarding dual citizenship. A normative juridical methodology is utilized in this research to explore the concept of citizenship from a constitutional viewpoint and compares Indonesia’s policies with those of other countries that recognize dual citizenship. The study finds that Indonesia’s current citizenship regulations need to be updated to be more adaptable and inclusive in addressing global changes. It is suggested that the Indonesian government consider revising its citizenship laws to better safeguard the rights of Indonesian citizens abroad and enhance connections with the diaspora.